Deconstructing the OSCE. - Harding, Duncan (Oxford specialty training., 2014)
The OSCE forms the practical part of educational and professional medical examinations and is often challenging and expensive. Deconstructing the OSCE takes a fresh approach to passing OSCE exams, teaching readers how to tackle the exam in a new way. This book doesn't provide checklists of information needed for specific OSCE stations; instead it helps readers to develop generic strategies and skills that will lead to success in any OSCE exam regardless of specialty orlevel. Packed full of advice, practical tips, real life examples and exercises, this book will prepare candidates with the skill.